Technique for measurement of UHF RFID balanced antennas - Peruzzi, Marcelo (2018)
A balun designed on laminated epoxy PCB to measure inductive ultrahigh- frequency-balanced antennas is presented. Its objective is to minimise the reflection coefficient at its unbalanced input when the antenna is connected to its balanced output. This improves the accuracy in the posterior extraction of the antenna parameters from the measurement of its reflection coefficient. Theoretical considerations, design parameters and experimental results with an evaluation antenna are shown.